(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article is devoted to the issues of using modern pedagogical technologies to develop students’ cognitive interest in mathematics in secondary schools. In the article, the ways of forming a deep interest and creative approach to the subject in students by using interactive methods, didactic games, multimedia tools, and other advanced technologies in the process of teaching mathematics are highlighted. Also, technological methods that help to increase students’ interest in mathematics and stimulate their cognitive activity, ways to improve the professional skills of teachers and increase the efficiency of the educational process are shown. This article is useful for educators, educational researchers and methodologists, and contains practical suggestions and recommendations that can be used to effectively develop students’ interest in learning mathematics.